Initial Evaluations of the Microtubule-Based PET Radiotracer, [11C]MPC-6827 in a Rodent Model of Cocaine Abuse - Damuka, Naresh; Martin, Thomas J.; Bansode, Avinash H.; Krizan, Ivan; Martin, Conner W.; Miller, Mack; Whitlow, Christopher T.; Nader, Michael A.; Solingapuram Sai, Kiran Kumar (Frontiers in Medicine, 2022)
Purpose Microtubules (MTs) are structural units made of α and β tubulin subunits in the cytoskeleton responsible for axonal transport, information processing, and signaling mechanisms—critical for healthy brain function. Chronic cocaine exposure affects the function, organization, and stability of MTs in the brain, thereby impairing overall neurochemical and cognitive processes. At present, we have no reliable, non-invasive methods to image MTs for cocaine use disorder (CUD). Recently we reported the effect of cocaine in patient-derived neuroblastoma SH-SY5Y cells. Here we report preliminary results of a potential imaging biomarker of CUD using the brain penetrant MT-based radiotracer, [11C]MPC-6827, in an established rodent model of cocaine self-administration (SA). Methods Cell uptake studies were performed with [11C]MPC-6827 in SH-SY5Y cells, treated with or without cocaine (n = 6/group) at 30 and 60 min incubations. MicroPET/CT brain scans were performed in rats at baseline and 35 days after cocaine self-administration and compared with saline-treated rats as controls (n = 4/sex). Whole-body post-PET biodistribution, plasma metabolite assay, and brain autoradiography were performed in the same rats from imaging. Results Cocaine-treated SH-SY5Y cells demonstrated a ∼26(±4)% decrease in radioactive uptake compared to non-treated controls. Both microPET/CT imaging and biodistribution results showed lower (∼35 ± 3%) [11C]MPC-6827 brain uptake in rats that had a history of cocaine self-administration compared to the saline-treated controls. Plasma metabolite assays demonstrate the stability (≥95%) of the radiotracer in both groups. In vitro autoradiography also demonstrated lower radioactive uptake in cocaine rats compared to the control rats. [11C]MPC-6827’s in vitro SH-SY5Y neuronal cell uptake, in vivo positron emission tomography (PET) imaging, ex vivo biodistribution, and in vitro autoradiography results corroborated well with each other, demonstrating decreased radioactive brain uptake in cocaine self-administered rats versus controls. There were no significant differences either in cocaine intake or in [11C]MPC-6827 uptake between the male and female rats. Conclusions This project is the first to validate in vivo imaging of the MT-associations with CUD in a rodent model. Our initial observations suggest that [11C]MPC-6827 uptake decreases in cocaine self-administered rats and that it may selectively bind to destabilized tubulin units in the brain. Further longitudinal studies correlating cocaine intake with [11C]MPC-6827 PET brain measures could potentially establish the MT scaffold as an imaging biomarker for CUD, providing researchers and clinicians with a sensitive tool to better understand the biological underpinnings of CUD and tailor new treatments.